Property relations and the co-management of small-scale fisheries in Costa Rica: Lessons from Marine Areas for Responsible Fishing in the Gulf of Nicoya. (November 2016) - García Lozano, Alejandro J.; Heinen, Joel T.
Abstract: Marine fisheries in Costa Rica have become characterized by overexploitation, ineffective centralized management and increased conflict among fishing sectors. Despite high economic and socio-cultural importance of small-scale fisheries, no formal mechanisms existed until recently to facilitate the participation of fishers in management. Marine Areas for Responsible Fishing ( Áreas Marinas para la Pesca Responsable, AMPR) were legally recognized in 2009 as a co-management approach, enabling the designation of spatial management areas to be implemented collaboratively by artisanal fishers and government agencies. In this paper, we examine property and access relations shaping this emerging participatory management model using case studies primarily from the Gulf of Nicoya region. The policy demonstrably improves upon some aspects of management, for instance, by allowing artisanal fishers to determine gear restrictions within designated areas. However, the model lacks other attributes of more successful co-management scenarios, particularly exclusive access. The fugitive nature of resources further complicates property relations over these fisheries. The cases explored also illustrate broader institutional and systemic issues that preclude effective participatory management. Lessons from the region are used to propose significant shifts to the management of small-scale fisheries in Costa Rica. Highlights: An emerging model for spatial co-management of small-scale fisheries is examined. Property and access relations are central to understanding this management model. Cases illustrate political will to solve access struggles and protect livelihoods. Lack of exclusivity and weak government support are identified as major challenges. Collaborative research and inter-agency coordination are key areas for improvement.